An Independent Evolutionary Origin for Insect Deterrent Cucurbitacins in Iberis amara. (15th July 2021) - Dong, Lemeng; Almeida, Aldo; Pollier, Jacob; Khakimov, Bekzod; Bassard, Jean-Etienne; Miettinen, Karel; Stærk, Dan; Mehran, Rahimi; Olsen, Carl Erik; Motawia, Mohammed Saddik; Goossens, Alain; Bak, Søren
Abstract: Pieris rapae and Phyllotreta nemorum are Brassicaceae specialists, but do not feed on Iberis amara spp. that contain cucurbitacins. The cucurbitacins are highly oxygenated triterpenoid, occurring widespread in cucurbitaceous species and in a few other plant families. Using de novo assembled transcriptomics from I. amara, gene co-expression analysis and comparative genomics, we unraveled the evolutionary origin of the insect deterrent cucurbitacins in I. amara . Phylogenetic analysis of five oxidosqualene cyclases and heterologous expression allowed us to identify the first committed enzyme in cucurbitacin biosynthesis in I. amara, cucurbitadienol synthase (IaCPQ). In addition, two species-specific cytochrome P450s (CYP708A16 and CYP708A15) were identified that catalyze the unique C16 and C22 hydroxylation of the cucurbitadienol backbone, enzymatic steps that have not been reported before. Furthermore, the draft genome assembly of I. amara showed that the IaCPQ was localized to the same scaffold together with CYP708A15 but spanning over 100 kb, this contrasts with the highly organized cucurbitacin gene cluster in the cucurbits. These results reveal that cucurbitacin biosynthesis has evolved convergently via different biosynthetic routes in different families rather than through divergence from an ancestral pathway. This study thus provides new insight into the mechanism of recurrent evolution and diversification of a plant defensive chemical.